Studi Fenomenologi Tim Redaksi Harian Haluan dan Singgalang di Era Disrupsi Informasi - Eriandi, Eriandi; Dewi, Rahmi Surya; Arif, Ernita (Jurnal Pustaka Komunikasi, 2023)
Print media is increasingly less attractive to the public. The presence of digital or online media has made news no longer dominated by print and electronic media. Online media and social media have won the hearts of the public in presenting news. The presence of new media as progress in information and communication technology creates disruptions in the information sector. This research describes and analyzes the experiences of the editorial team of Haluan Daily and Singgalang Daily in the midst of information disruption. This research uses the concept of Edmund Husserl's Phenomenological Theory, where the experience of communication between sub-organizations, between individuals and groups within the editorial office of local daily newspapers, Harian Haluan and Harian Singgalang in Padang, West Sumatra, amidst information disruption. Data were obtained from interviews with informants, books, articles, and other related literature. The purpose of this research was to find out the communication experiences of the editorial work team of Haluan Daily and Singgalang Daily in the midst of information disruption and the meaning of information disruption. The method used in this research is qualitative. The results of the study obtained communication experience in the form of assignments, work team communication, work results and work comfort.